The Mediating Role of Work Motivation on the Influence of Work Life Balance and Work Motivation on Employee Performance in Generation Z - Purnamasari, Dewi; Soebandono, Joni Pasifiano (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The purpose of this study was to examine the effect of Work Life Balance and Work Motivation on employee performance in Gen Z employees with the mediating role of Work Motivation. The population in this study were generation Z employees, namely employees born in 1995-2006 and working in private companies with a sample of 226 respondents. The sampling technique used in this study was purposive sampling technique. then CFA testing and path analysis were carried out using Mplus software. The results showed that all dimensions of Work Life Balance had no effect on Employee Performance, but Career Development had a significant effect on Employee Performance and Work Motivation proved to be a mediator between the influence of Career Development and Employee Performance. Therefore, it is recommended that companies pay more attention and learn how to improve employee career development in order to improve the performance of generation Z employees.